The state of the art of financial exclusion (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The aim of this study is to provide an umbrella vision and synthesized on thestudy of financial exclusion that has been conducted to date, allowing the theoretical framework to identify and understand the state of the art of it. To do so, it shall be thorough analysis of the conceptualization of financial exclusion, ther by determining the reality that has tried to analyze in different empirical studies, to then classify the range of studies that have been done on it.
Keywords: Financial exclusion; financial services; socioeconomic description.